On the Relation Between Marr's Levels: A Response to Blokpoel (2017). (13th July 2017) - Cooper, Richard P.; Peebles, David
Abstract: Blokpoel reminds us of the importance of consistency of function across Marr's levels, but we argue that the approach to ensuring consistency that he advocates—a strict relation through exact implementation of the higher level function at the lower level—is unnecessarily restrictive. We show that it forces overcomplication of the computational level (by requiring it to incorporate concerns from lower levels) and results in the sacrifice of the distinct responsibilities associated with each level. We propose an alternative, no less rigorous, potential characterization of the relation between levels.